EVALLUTION OF TWO VACCINATION SCHEDULES FOR NEWCASTLE AND INFECTIOUS BURSAL DISEASE - Ali; Nadim; Harith; Dina; A.K; A.N-ALTaher; A.S; A.H; A.S.AL-Mayah; Qasire; H.S. and Ehsan (Basrah Journal of Veterinary Research)
The aim of this study was to determine the interaction between the Newcastle disease and Infectious bursal disease vaccines commonly used in the field to control these two important viral diseases. Haemagglutination inhibition (HI) test was employed to measure the antibody titers in chicks sera to ND.IBD vaccine was showed to have adverse effect on the ND vaccine were as the reverse was not true. The results obtained also revealed that better antibody response against ND vaccine was detected when ND vaccine was administered before IBD vaccine. The deleterious effect of IBD vaccine on antibody levels against ND vaccine was low when IBD vaccine was administered at 14 days of age as compared to 7 days of chicken age. No great variation in the antibody titers when chicks were administered ND vaccine containing LaSota or Hitchner B1strain of the virus were observed, although slight better antibody responses were noted for LaSota over HitchnerB1 strain. Vaccination of chicks with ND vaccine of LaSota strain at 7 days followed by vaccination with IBD vaccine at 14 days yielded better antibody titers than Hitchner B1.